Sharing the ecological knowledge of plants used in handicrafts as a survival strategy of rural communities of Dera Ghazi Khan district, Pakistan - Sajjad, Muhammad; Abbas, Zaheer; Khan, Shujaul Mulk; Abdullah, Abdullah; Yoo, Sunghoon; Han, Heesup; Raposo, António; Bussmann, Rainer W. (Ethnobotany Research and Applications, 2024)
Background: Craftwork is one of the vital components of phyto-culture worldwide. It offers a livelihood to marginalized communities in the rapidly changing environmental conditions with the preservation of cultural diversity. This study aimed to evaluate the indigenous knowledge about the utilization and cultural importance of plant-based handicrafts in the rural communities of Dera Ghazi Khan District, Pakistan. Methods: In order to collect the desired data preliminary, surveys and field trips were carried out in sixteen remote sites of the study area from September 2021 to May 2022. Altogether, 105 respondents were sampled via snow-boll sampling techniques. Semi-structured interviews with open-ended questions were employed after getting verbal consent. The participants were evaluated for their ethnicity, age, language, education, and livelihood. The status, challenges and transmission of traditional knowledge were also assessed. Results: Five plant taxa were recorded for craftwork, i.e., Saccharum bengalense Retz.(Poaceae), Phoenix dactylifera L., Nannorrhops ritchieana (Griff.) Aitch. (Arecaceae), Typha latifolia L. (Typhaceae), and Tamarix aphylla (L.) H.Karst. (Tamaricaceae). These species grow around wetlands and only Phoenix dactylifera L. was cultivated species. The participants cited 49 handicraft products manufactured from the reported species. Maximum products (14. 28%) were made from the raw materials of Phoenix dactylifera L. followed by Nannorrhops ritchieana (Griff.) Aitch. (12, 24%), Typha latifolia L. (9, 18%), and Saccharum bengalense Retz.(8, 16%) and Tamarix aphylla (L.) H.Karst. (6, 12%). All these handicraft products were in rough and limited marketing loop. The documented species were also valued for traditional therapies of 25 diseases related to respiratory, digestive, urinary, dermal and cardiovascular systems. Relative frequency citations (RFCs) were ranged from 0.17 – 0.24 for calculated for Nannorrhops ritchieana (Griff.) Aitch. and Phoenix dactylifera L. respectively. Conclusion: Similarly, in the current era of modernization, the traditional knowledge of crafting plants is seemingly underappreciated. Although it is still in practice with subjection to limitation, fragmentation, and eroding. In this regard, social discouragement, harsh socio-ecology, modern life patterns and shifting earning trends are potential factors for its depletion. Inclusion of this valued knowledge in school syllabi, development of vocational centers, and devising of a proper market chain could be game changers for revitalization and achievement of sustainable development goals for these impoverished but professional communities. Keywords: Phytoculture, marginalized communities, craftworks, livelihood, modernization